Autothermal reforming of methane to hydrogen in a palladium membrane reactor: characterization of bimetallic Pt-NiO/delta-Al2O3 catalyst - Songip, Ahmad Rahman; Nasri, N. S.; Jungan, J. (Universiti Teknologi Petronas, 2004)
A bimetallic Pt(0.2)-Ni(25)/delta-Al2O3 (wt/wt%) was prepared by incipient wetness technique. The catalyst was characterized by X-ray diffraction (XRD) and Temperature-programmed reduction (TPR) analysis. The catalyst characterization results showed that doping of Pt catalyses the complete reduction of Ni2+ to Ni0 and a bimetallic surface interaction was formed. The NiAl2O3 spinel phases were observed and reduced at lower temperatures.